2015
DOI: 10.1016/j.micromeso.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of phenols with methylbutenol over MOFs: The role of catalyst structure and acid strength in producing 2,2-dimethylbenzopyran derivatives

Abstract: Elsevier Shamzhy, MV.; Opanasenko, MV.; García Gómez, H.; Cejka, J. (2015). Annulation of phenols with methylbutenol over MOFs: The role of catalyst structure and acid strength in producing 2,2-dimethylbenzopyran derivatives. Microporous and Mesoporous Materials. 202:297-302. doi:10.1016/j.micromeso.2014.10.003. AbstractThe catalytic behavior of metal-organic frameworks of different structures (Fe(BTC), MIL-100 (Fe), MIL-100(Cr) and Cu 3 (BTC) 2 ) was investigated in annulation reaction between 2-methyl-3-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Maybe this fact has significantly contributed to make it one of the most widely studied MOFs as catalysts [50,[51][52][53][54][55][56][57], despite its structure is still unknown and its direct preparation has been described only two years ago [51]. Finally, Fe-BTC offers two key advantages when used as potential support for enzymes: (i) Fe is a biocompatible and safe metal ion for human beings, so the resultant biocatalysts can be used in any application including food industry, biomedicine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe this fact has significantly contributed to make it one of the most widely studied MOFs as catalysts [50,[51][52][53][54][55][56][57], despite its structure is still unknown and its direct preparation has been described only two years ago [51]. Finally, Fe-BTC offers two key advantages when used as potential support for enzymes: (i) Fe is a biocompatible and safe metal ion for human beings, so the resultant biocatalysts can be used in any application including food industry, biomedicine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this material has been used as a raw material to generate highly active and stable Fischer–Tropsch catalysts . It is particularly noteworthy that its catalytic behavior has been systematically compared with that of the well-known MIL-100­(Fe) in a large number of reactions. ,,,,, MIL-100­(Fe) material is also formed by iron and trimesic acid; that is, it is also a Fe-BTC material, having two types of cages in the range of mesopores . Wide and detailed comparison between both materials concluded that they are similar but essentially different from a physicochemical point of view .…”
Section: Introductionmentioning
confidence: 99%
“…This solvent molecule can be easily removed 2 of 11 by thermal treatment under vacuum without damaging the crystal structure, generating coordinatively unsaturated positions around Cu 2+ that are able to activate substrates and reagents [24]. The structure of Cu 3 (BTC) 2 is shown in Scheme 1 [25]. These metal nodes and linkers define large cavities in a highly open structure with a high surface area (~1300 m 2 /g) and porosity (1.6 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Structure of Cu 3 (BTC) 2 . Reproduced with permission from[25]. Copyright 2015 Elsevier.…”
mentioning
confidence: 99%